1998
DOI: 10.1093/ageing/27.6.697
|View full text |Cite
|
Sign up to set email alerts
|

Risk of admission within 4 weeks of discharge of elderly patients from the emergency department—the DEED study

Abstract: older patients are at increased risk of readmission within 4 weeks of being sent home from the emergency department. It is possible to identify high-risk patients by a questionnaire. This allows targeting of these patients for more intensive follow-up in an attempt to ameliorate further deteriorations in their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
117
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 11 publications
7
117
1
2
Order By: Relevance
“…[1][2][3][4] Furthermore, they have a longer average length of stay and greater risks of adverse events, as functional decline, in-hospital death and rehospitalization after discharge. 1,3,[5][6][7] We previously showed that the elderly account for a high proportion of multiple hospital admissions. This fact is mainly as a result of poor health conditions, such as high comorbidity, presence of chronic multi-organ diseases and functional dependence.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Furthermore, they have a longer average length of stay and greater risks of adverse events, as functional decline, in-hospital death and rehospitalization after discharge. 1,3,[5][6][7] We previously showed that the elderly account for a high proportion of multiple hospital admissions. This fact is mainly as a result of poor health conditions, such as high comorbidity, presence of chronic multi-organ diseases and functional dependence.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Older patients are more likely to experience adverse events in the ED, 8 including iatrogenic injury, 9 missed diagnoses, 10 omitted treatments, [11][12][13] poor medical outcomes, 14,15 death, 16 functional decline, [17][18][19] prolonged stays, 16 necessity for a discharge to a higher level of care, 20 and repeat ED use. 21,22 A 1992 American study reported that EPs found it challenging to provide consistently high-quality care for older patients. 23 Improving the balance between rapid flow and optimal outcomes in the geriatric population may require both readjustment of the model of care for older adults 7 and disruptive innovation-beginning with geriatric emergency medicine education.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are not admitted as inpatients frequently suffer a deterioration in their condition, and up to 20% will re-present or be admitted within 1 month of discharge. 4 Those who are discharged home from the ED often express apprehension about their ability to manage after discharge. 3 In a study of ED usage by older Australians, Richardson reported that one of the strongest predictors of death or increased dependency within 3 months of discharge was found in presentations where social factors were of concern.…”
mentioning
confidence: 99%